SOLAR ENERGY APPLICATION FOR FARM ENTERPRISES ELECTRICAL MAINTENANCE (Academic journal Industrial Machine Building Civil Engineering, 2017)
Features of livestock houses designing for rural (farm) enterprises with observance ofsanitary standards have been described; expensiveness of the design phases, construction andinstallation works and electricity generation equipment in such buildings is emphasized.Foreign experience in solar cell batteries application has been analyzed. Advantages anddisadvantages of the renewable power sources setting up have been determined, particularlyconcerning the first few years of operation. The dynamics of the energy-intensive equipmentinstallation at farm enterprises of Ukraine has been analyzed, a trend of implementinginnovative technologies as an autonomous, maximally independent energy supply source, hasbeen detected. The environmental safety of such energy supply solution and its installationefficiency in any region is emphasized. The possibility is considered for alternative energysupply sources application and energy supply independence of cooperated livestock houses atfarm enterprises, particularly under the conditions of persistent reduction in prices for photoelectricmodules and persistent growth of gas and electricity rates.Keywords: livestock house, farm enterprise, natural energy sources, solar cell batteries.